Using TSF Multi-Planar External Fixation for Overcorrection of Severe Equinus Contractures of the Ankle joint. Issue 4 (16th October 2019) - Dabash, Sherif; Potter, Eric; McGarvey, William
Category: Ankle, Hindfoot, Trauma Introduction/Purpose: Equinus deformity is a debilitating condition which interferes with the activity of daily living. Correction of the deformity ranges from conservative (heel cord stretching, orthotics) to surgical treatment (Baumann, Strayer, Achilles lengthening, soft tissue releases). Severe contractures need surgical intervention with extensive dissections to release soft tissues. This study investigated the clinical outcomes of gradual equinus contracture overcorrection using a Taylor Spatial Frame with tendo-Achilles lengthening or toe flexor tenotomy as necessary. Methods: This retrospective chart review evaluated patients with significant equinus treated with a Taylor Spatial Frame at a single large tertiary referral center. Data collected included: diagnosis; patient demographics; laterality; time in frame; additional procedures; complications. Patients were assessed preoperatively and were followed at one-week, three-week, six-week, three- month, and six-month intervals, and yearly after. Results: 24 patients (26 procedures) were treated with a Taylor Spatial Frame for equinus and had complete preoperative and eighteen-month follow-up measurements. The angle of deformity increased from a preoperative -21.5 (range, -69.0 to -1.0) degrees to a postoperative 4.9 (range, -17.0 to 17.0) degrees (z = -4.4573, p = 0.0001, N = 26, Wilcoxon signed rank test). Four complications occurred during the follow up (two pin site infections, one broken pin, and one plantar abscess). Three patients had recurrence of of equinus deformity at time of last follow-up. Conclusion: Taylor Spatial Frame is a successful method for correcting severe, fixed equinus contractures of the ankle joint with minimal soft tissue related complications. Over correction should be achieved in order to compensate for the loss of some dorsiflexion after frame removal.